Promoting Sustainable Seafood Market in Japan: Perspectives From MSC and ASC Applicants - Ishihara, Hiroe; Blandon, Abigayil; Watanabe, Juri; Yagi, Nobuyuki (Frontiers in Sustainable Food Systems, 2022)
Japanese seafood market has witnessed a slow but steadfast increase in the amount of certified seafood circulated on the market despite the fact that there are few incentives to apply for certification schemes such as the Marine Stewardship Council (MSC) and the Aquaculture Stewardship Council (ASC). This is because it is difficult for the producers to reap benefits from the price premium as the retailers are unwilling to charge the consumers a higher price for the certified seafood; at the same time, there are no sourcing codes set by the retailers to ban the access of uncertified seafood. By conducting semi-structured interviews with the applicants of MSC and ASC, this study reveals the motivation of the applicants such as the desire of producers to differentiate their seafood products from similar products on the market and to establish stable distribution channels with large retailers. We argue that this type of motivation poses a unique challenge in promoting sustainable seafood in Japan, that is the certified product needs to remain a small proportion of circulated seafood products.